Corticospinal Excitability Is Modulated as a Function of Postural Perturbation Predictability - Fujio, Kimiya; Obata, Hiroki; Kitamura, Taku; Kawashima, Noritaka; Nakazawa, Kimitaka (Frontiers in Human Neuroscience, 2018)
Recent studies demonstrated that the corticospinal pathway is one of the key nodes for the feedback control of human standing and that the excitability is flexibly changed according to the current state of posture. However, it has been unclear whether this pathway is also involved in a predictive control of human standing. Here, we investigated whether the corticospinal excitability of the soleus (SOL) and tibialis anterior (TA) muscles during standing would be modulated anticipatorily when perturbation was impending. We measured the motor-evoked potential (MEP) induced by transcranial magnetic stimulation over the motor cortex at six stimulus intensities. Three experimental conditions were set depending on predictabilities about perturbation occurrence and onset: No perturbation, No Cue, and Cue conditions. In the Cue condition, an acoustic signal was given as timing information of perturbation. The slope of the stimulus–response relation curve revealed that the TA-MEP was enhanced when postural perturbation was expected compared to when the perturbation was not expected (No Perturbation vs. No Cue, 0.023 ± 0.004 vs. 0.042 ± 0.007; No Perturbation vs. Cue, 0.023 ± 0.004 vs. 0.050 ± 0.009; Bonferroni correction, p = 0.01, respectively). In addition, two-way analysis of variance (intensity × condition) revealed the main effect of condition (F(1,13) = 6.31, p = 0.03) but not intensity and interaction when the MEP amplitude of the Cue and No Cue conditions was normalized by that in No Perturbation, suggesting the enhancement more apparent when timing information was given. The SOL-MEP was not modulated even when perturbation was expected, but it slightly reduced due to the timing information. The results of an additional experiment confirmed that the acoustic cue by itself did not affect the TA- and SOL-MEPs. Our findings suggest that a prediction of a future state of standing balance modulates the corticospinal excitability in the TA, and that the additional timing information facilitates this modulation. The corticospinal pathway thus appears to be involved in mechanisms of the predictive control as well as feedback control of standing posture.